The Relationship between Nurse Oversight and the Compliance of Nurses to Dispose Medical and Non-Medical Waste in Padang Lawas Hospital - Dewi Astuti Pasaribu (Institute of Computer Science (IOCS), 2019)
Prevent and infection control nurses are a professional and practitioner in hospitals and other health facilities. Based on the health ministry, every hospital must prevent transmission of infection. Nurse adherence is an intervention to separate medical garbage exactly. This research is quantitative correlational research aimed at analyzing correlation supervision of infection prevention control nurses with adherence managing medical and non-medical waste in Padang Lawas Hospital year 2018 with samples was 37 respondents. The results of the research obtained that 28.6% or 18 respondents of supervision performed by IPCN nurses were moderate and 18.9% or 7 respondents of supervision performed by IPCN nurses were less good. Nurses adherence good medical and nonmedical waste management was 22 respondents (59.5%). It was concluded that any correlation between the infection Prevention Control Nurse supervision and nurse adherence medical and nonmedical waste management (p value = 0.001). it is recommended that IPCN nurses provide more supervision until the low infection rate in hospitals.